Determination of Melatonin by Differential Pulse Voltammetry at Modified Carbon Paste Electrode - Bekheit, G.E. (Asian Journal of Chemistry, 2010)
A direct sensitive and reproducible electroanalytical procedure for the determination of melatonin is developed at a modified and unmodified carbon paste electrode. A linear relationship between the current and concentration was found at the two electrode surfaces. The method was employed for the analysis of melatonin in urine samples. The open circuit preconcentration/medium exchange/voltammetric scheme was used to eliminate interference from sample solutions.